Singing can facilitate foreign language learning. - Ludke, Karen; Ferreira, Fernanda; Overy, Katie (Memory & Cognition, 2014)
This study presents the first experimental evidence that singing can facilitate short-term paired-associate phrase learning in an unfamiliar language (Hungarian). Sixty adult participants were randomly assigned to one of three 'listen-and-repeat' learning conditions: speaking, rhythmic speaking, or singing. Participants in the singing condition showed superior overall performance on a collection of Hungarian language tests after a 15-min learning period, as compared with participants in the speaking and rhythmic speaking conditions. This superior performance was statistically significant ( p < .05) for the two tests that required participants to recall and produce spoken Hungarian phrases. The differences in performance were not explained by potentially influencing factors such as age, gender, mood, phonological working memory ability, or musical ability and training. These results suggest that a 'listen-and-sing' learning method can facilitate verbatim memory for spoken foreign language phrases.